2019
DOI: 10.1101/627851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skeletal muscle stem cell self-renewal and differentiation kinetics revealed by EdU lineage tracing during regeneration

Abstract: Skeletal muscle maintenance and repair is dependent on the resident adult muscle stem cell (MuSC). During injury, and in diseased muscle, stem cells are engaged to replace or repair damaged muscle, which requires the stem cells to exit quiescence and expand, followed by differentiation to regenerate myofibers and self-renewal to replenish the stem cell population.Following an injury, little is known regarding the timing of MuSC (skeletal muscle stem cell) self-renewal, myoblast expansion or myoblast differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In addition, our analyses show that MuSCs perform mostly self-renewing SCDs at 3 dpi, while they can execute SCDs and ACDs at 5 dpi. These observations indicate that MuSCs can switch from SCDs to ACDs in vivo between 3 and 5 dpi, and this correlates with a decrease in their proliferative potential (Joe et al, 2010;Pawlikowski et al, 2019). Our complementary ex vivo studies tracking single cells over consecutive cell divisions revealed an unexpected switch from ACD to SCD.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, our analyses show that MuSCs perform mostly self-renewing SCDs at 3 dpi, while they can execute SCDs and ACDs at 5 dpi. These observations indicate that MuSCs can switch from SCDs to ACDs in vivo between 3 and 5 dpi, and this correlates with a decrease in their proliferative potential (Joe et al, 2010;Pawlikowski et al, 2019). Our complementary ex vivo studies tracking single cells over consecutive cell divisions revealed an unexpected switch from ACD to SCD.…”
Section: Discussionmentioning
confidence: 57%
“…A recent study on muscle regeneration identified time windows of MuSC self-renewal and differentiation (Pawlikowski et al, 2019). To date, direct measurement of MuSC modes of cell division in vivo with single-cell resolution is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this model, Chakkalakal et al have previously identified two populations of MuSCs in vivo-one that divides frequently and one that that only undergoes rare cell divisions (Chakkalakal et al, 2014). Furthermore, in vivo EdU incorporation experiments at specific time points after muscle injury have shown that 75% of quiescent MuSCs that reside on myofibers have extensively proliferated between the time of injury and their homing in the myofiber niche (Pawlikowski et al, 2019). Thus, we propose that progenitor amplification and return to quiescence is a major mechanism underlying MuSC niche repopulation upon injury, and that it occurs in parallel with asymmetric division of naive MuSC.…”
Section: Discussionmentioning
confidence: 81%
“…Of all the impaired resident cells in degenerative cuff tendons, the senescence of TSPCs causes arguably the most detrimental effects of inflamm-aging, such as self-renewal defects and decreased differentiation potential to regenerate tenocytes. [17][18][19] In this study, we revealed that senescent TSPCs accumulate in degenerative rotator cuff tendons, which may serve as a potential therapeutic target for treating degenerative RCT. 20,21 Several studies have reported that the intrinsic pathogenic mechanisms of tendon degeneration can be traced back to TSPC senescence and dysfunction 6,11,22,23 ; however, the intrinsic mechanisms underlying TSPC senescence are still unknown.…”
Section: Discussionmentioning
confidence: 73%